Ray propagation imaging and optical quality evaluation of different intraocular lens models - Son, Hyeck Soo; Łabuz, Grzegorz; Khoramnia, Ramin; Merz, Patrick; Yildirim, Timur Mert; Auffarth, Gerd U. (PLOS ONE, 2020)
Purpose: Ray propagation visualization and optical performance analysis of four different intraocular lenses (IOLs) Methods In this laboratory study, four IOLs with different optical designs were assessed: a monofocal AcrySof IQ SN60WF [Alcon], a diffractive-refractive bifocal AcrySof IQ Restor SN6AD1 [Alcon], a diffractive trifocal AcrySof IQ PanOptix TFNT00 [Alcon], and a diffractive extended-depth-of-focus (EDOF) Symfony ZXR00 [Johnson&Johnson]. An experimental set-up with a water bath containing 0.01% fluorescein solution and monochromatic green laser light (532 nm) was used to visualize the propagation of light rays. Also, the optical performance of the IOLs was evaluated by measuring the modulation transfer function (MTF) values at a pupil sizes of 3.0 and 4.5 mm on the optical bench OptiSpheric® IOL PRO II (Trioptics GmbH, Germany). Results Both the diffractive-refractive bifocal IOL and the EDOF IOL showed two defined foci for distance and near vision. In the diffractive trifocal IOL, three distinct foci for distance, intermediate, and near vision could be visualized. Conclusions: The ray propagation visualization technique allows a qualitative assessment and comparison of light energy distribution between different IOL models. The measured Through-Focus Response (TFR) quantitatively confirmed the evaluated ray propagation behavior.
Gesehen am 15.06.2020